New York Regents External Degree Bachelor of Science (Nursing) Degree Description (Distributed by ERIC Clearinghouse, 1978)
The New York State Board of Regents offers an off-campus bachelor of science degree in nursing equivalent to a campus-based four-year nursing program. Described in detail are its general education component, nursing component, and how to begin the program. A list of approved equivalency examinations is included. (MSE)